Waldenstrom Macroglobulinemia Presenting with Pancreatic Mass: A Case Report and Review of Literature - Nayak, Hemanta Kumar; Kar, Premashish; Bagchi, Avishek; Kapoor, Neha; Kapahtia, Siddarth; Sonika, Ujjwal; Kumar, Naresh; Kumar, Suresh (JOP. Journal of the Pancreas, 2013)
Context Waldenstrom macroglobulinemia is a rare lymphoplasmacytic lymphoma characterized by a wide range of clinical presentations related to direct tumor infiltration and the production of IgM. Most commonly it presents with cytopenia, hepatosplenomegaly, lymphadenopathy, constitutional symptoms, and hyperviscosity syndrome. Case report We report a case of Waldenstrom macroglobulinemia in an 60-year-old female who initially presented with intermittent abdominal pain. The patient had no peripheral lymphadenopathy. On extensive investigation she was found to have pancreatic mass. The diagnosis of Waldenstrom macroglobulinemia was established after cytomorphology and immunohistochemical analysis of the patient’s bone marrow revealed the presence of a lymphoid/lymphoplasmacytoid-like bone marrow infiltrate along with an elevated serum IgM level. The patient responded both clinically and serologically to chemotherapy. This case is unusual because the patient lacked all common clinical features of Waldenstrom macroglobulinemia with exception of anemia. Conclusion To our knowledge this is the first report of a patient with Waldenstrom macroglobulinemia presenting with a pancreatic mass adding to the spectrum of clinical presentations seen in this disease. This adds to the wide variety of gastrointestinal related clinical presentations of Waldenstrom macroglobulinemia and points to the need for considering Waldenstrom macroglobulinemia along with other lymphoid neoplasms in the differential diagnosis of pancreatic lesions. Image: A sharp M band in the gamma-globulin region detected on serum protein electrophoresis.